(untitled) (Swiss Medical Weekly, 2017)
QUESTION Extreme prematurity can result in long-term disabilities. Its impact on society is often not taken into account and deemed controversial. Our study examined attitudes of the Swiss population regarding extreme prematurity and people’s perspectives regarding the question of solidarity with disabled people. METHODS We conducted a nationwide representative anonymous telephone survey with 1210 Swiss residents aged 18 years or older. We asked how people estimate their own personal solidarity, the solidarity of their social environment and the solidarity across the country with disabled persons. Spearman’s correlation calculations were used to assess if a correlation exists between solidarity and setting financial limits to intensive care and between solidarity and withholding neonatal intensive care. RESULTS According to 36.0% of the respondents intensive medical care should not be withheld from extremely preterm infants, even if their chances for an acceptable quality of life were poor. For 28.8%, intensive care should be withheld from these infants, and 26.9% held an intermediate position depending on the situation. A total of 31.5% were against setting a financial limit to treatment of extremely preterm newborns with an uncertain future quality of life, 34.2% were in favour and 26.9% were deliberating. A majority (88.8%) considered their solidarity toward disabled people as substantial; the solidarity of their personal environment and of the society at large was estimated as high by 79.1% and 48.6%, respectively. CONCLUSIONS The Swiss population expressed a high level of solidarity which may alleviate some pressure on parents and health care providers in the decision-making process in neonatal intensive care units. In addition, there was no relationship between solidarity and people’s willingness to pay for the care or withholding treatment of extremely preterm babies.